Electrochemical sensor based on screen printed carbon electrode–zinc oxide nano particles/molecularly imprinted-polymer (SPCE–ZnONPs/MIP) for detection of sodium dodecyl sulfate (SDS). Issue 2 (24th December 2021) - Faradilla, Putri; Setiyanto, Henry; Manurung, Robeth Viktoria; Saraswaty, Vienna
Abstract : The foremost objective of this work is to prepare a novel electrochemical sensor-based screen-printed carbon electrode made of zinc oxide nanoparticles/molecularly imprinted polymer (SPCE–ZnONPs/MIP) and investigate its characteristics to detect sodium dodecyl sulfate (SDS). Abstract : The foremost objective of this work is to prepare a novel electrochemical sensor-based screen-printed carbon electrode made of zinc oxide nanoparticles/molecularly imprinted polymer (SPCE–ZnONPs/MIP) and investigate its characteristics to detect sodium dodecyl sulfate (SDS). The MIP that is polyglutamic acid (PGA) film was synthesized via in situ electro-polymerization. The SDS's recognition site was left on the surface of the PGA film after extraction using the cyclic voltammetry (CV) technique, facilitating the specific detection of SDS. Moreover, the ZnONPs (∼71 nm, polydispersity index of 0.138) were synthesized and effectively combined with the MIP by a drop-casting method, enhancing the current response. The surface of the prepared SPCE–ZnONPs/MIP was characterized by scanning electron microscopy and energy dispersive X-ray. Besides, the electrochemical performance of the SPCE–ZnONPs/MIP was also studied through CV and differential pulse voltammetry (DPV) techniques. As an outstanding result, it is observed that the current response of SPCE–ZnONPs/MIP for detection of SDS remarkably increased almost four times higher from 0.009 mA to 0.041 mA in comparison with bare SPCE. More importantly, the proposed SPCE–ZnONPs/MIP exhibited an excellent selectivity (in the presence of interfering molecules of Ca 2+, Pb 2+, as well as sodium dodecylbenzene sulfonate (SDBS)), sensitivity, reproducibility, and repeatability. Since the modified sensor offers portability, it is suitable for in situ environment and cosmetic monitoring.